Functional hydrogel microspheres: Parameters affecting electrostatic assembly of biopolymer particles fabricated from gelatin and pectin. (June 2015) - Wu, Bi-cheng; McClements, David Julian
Abstract: Hydrogel microspheres may be used for various applications within foods, cosmetics, and pharmaceuticals, such as texture modification, encapsulation, or controlled release. The aim of this research was to examine the key parameters affecting the formation and properties of hydrogel microspheres fabricated by electrostatic complexation of gelatin and pectin. Hydrogel microspheres were formed by mixing 0.5 wt% gelatin and 0.01 wt% pectin at pH 10.0 and 30 °C, and then acidifying to pH 5.0 with continuous stirring. The effects of salt content (0–100 mM NaCl), shear rate (150–600 rpm), and acidification rate (fast, medium, and slow) on the formation and properties of the hydrogel microspheres were investigated. Increased salt content perturbed the complexation process due to electrostatic screening and ion-binding effects, which meant that lower pH values were needed to induce complexation. Optical microscopy and static light scattering showed that salt content also altered hydrogel particle microstructure. The largest particles were formed at an intermediate shear rate (300 rpm), which was attributed to the influence of shearing on mixing, particle disruption, and particle coalescence. Hydrogel microsphere size decreased as the acidification rate increased, which was attributed to an alteration in the balance of particle formation and particle growth. The parameters identified in this study facilitate the design of hydrogel microspheres with specific sizes and morphologies, which might be useful for tailoring their functional properties for different commercial applications. Highlights: Hydrogel microspheres formed by electrostatic assembly of gelatin and pectin. Salt altered the microstructure of hydrogel particles. Shear and acidification rate influenced hydrogel microsphere size.